Mircea Eliade and the Perception of the Sacred in the Profane: Intention, Reduction, and Cognitive Theory - BRYAN S. RENNIE (Temenos, 2007)
Building upon earlier analysis of Eliade's 'sacred' as 'the intentional object of human experience that is apprehended as the real' (Rennie 1996, 21) this article pursues the concept of the apprehension of the sacred in empirical experience as described by Eliade in his discussion of religious symbols. Using a vareity of visual analogies an attempt is made to understand what Eliade's understanding might imply and how this 'perception of the sacred' might come about. This necessitates some consideration of the status of 'intentional objects' and leads to a reflection on Eliadean claims concerning the 'irreducibility' of religion and of the relation of such claims to contemporary congnitive analyses of religion. The conclusion is that Eliade's understanding can be seen as complementary to recent cognitive theory, which demonstrates the coherence of that understanding.